Memanfaat Teknologi Pendidikan di Era Digital Pada Mata Pelajaran IPS di SD Negeri Alue Lhok - jannati, putri (Jurnal Aktual Pendidikan Indonesia, 2025)
Social studies education covers themes from social sciences, humanities, science and social issues in daily life. Information technology plays an important role in improving the effectiveness of social studies learning by providing various learning media and online platforms. This research applies a qualitative method, which combines a literature review with a descriptive investigation. This article investigates the benefits of educational technology in the context of social studies learning, such as improving access to learning resources, enabling distance learning, and enriching the learning experience through simulation and visualization. In addition, technology enables customized learning, accelerates the learning process, and improves the relationship between students and teachers. However, the use of technology in social studies learning also faces some obstacles, such as difficulties in programming, finding supporting materials, and limited teacher skills. To overcome these obstacles, adequate teacher training and appropriate strategies in developing technology-based learning media are needed. Thus, involving information technology into social studies learning in elementary schools can improve the quality of education while preparing students to face an increasingly advanced technological world.